2013
DOI: 10.1007/s00773-013-0233-2
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments and new design of a spilled oil tracking autonomous buoy

Abstract: It is important to forecast the location of oil spills to realize effective and adequate oil spill response operations when huge oil spilsl occur. In order to enhance the accuracy of oil drifting simulations, one needs to obtain the meteorological and oceanographic data around the oil slick. In general, the drifting velocity vector of an oil spill contains a wind velocity vector and a water current velocity vector. SOTAB-II was developed for autonomous tracking of oil slicks drifting on the sea surface. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…While the SOTAB-I collects rough data on physical and chemical characteristics of plumes, consisting of spilled out oil and gas, SOTAB-II USVs track the spilled oil on the sea surface. Also using SOTAB-I and SOTAB-II, Senga et al [111,112] perform experiments in Biwa Lake and Osaka Bay, Japan, to verify the effectiveness of sail and sail control for tracking oil plumes. Experiments indicate that once the buoy is dropped into the oil slick drifting on the sea surface, it sets out to drift with the oil slick using the wind force by effectively controlling the sail size and direction.…”
Section: Use Of Usvs In Environmental Disasters With Contaminantsmentioning
confidence: 99%
“…While the SOTAB-I collects rough data on physical and chemical characteristics of plumes, consisting of spilled out oil and gas, SOTAB-II USVs track the spilled oil on the sea surface. Also using SOTAB-I and SOTAB-II, Senga et al [111,112] perform experiments in Biwa Lake and Osaka Bay, Japan, to verify the effectiveness of sail and sail control for tracking oil plumes. Experiments indicate that once the buoy is dropped into the oil slick drifting on the sea surface, it sets out to drift with the oil slick using the wind force by effectively controlling the sail size and direction.…”
Section: Use Of Usvs In Environmental Disasters With Contaminantsmentioning
confidence: 99%
“…From the analysis of field experiments using the basic type of SOTAB-II, it was concluded that the sail control system of SO-TAB-II works well, but SOTAB-II with a cylindrical hull can't reach the target drifting speed [12]. As for the drifting function, SOTAB-II installed with a bigger sail may meet the required drifting speed.…”
Section: Design Of Sotab-iimentioning
confidence: 99%
“…If the drag force on SOTAB-II is so big, the auxiliary propulsion mechanism uses large electricity to bring SOTAB-II a certain location. Therefore, we design a new model of SOTAB-II with a yacht shape to reduce the drag coefficient in water [12].…”
Section: Design Of Sotab-iimentioning
confidence: 99%
“…However, the SOTAB-I is still not suitable for long-distance travel due to the use of propellers. To improve long-distance travel, the SOTAB-II [10] uses a sail and oscillating fins to control the buoy motion. Due to the use of sails and oscillating fins, the mechanics of SOTAB-II is more complex than other traditional buoys.…”
Section: Introductionmentioning
confidence: 99%